Cerebellar Lobulus Simplex and Crus I Differentially Represent Phase and Phase Difference of Prefrontal Cortical and Hippocampal Oscillations - Samuel S. McAfee; Yu Liu; Roy V. Sillitoe; Detlef H. Heck (Cell Reports, 2019)
Summary: The cerebellum has long been implicated in tasks involving precise temporal control, especially in the coordination of movements. Here we asked whether the cerebellum represents temporal aspects of oscillatory neuronal activity, measured as instantaneous phase and difference between instantaneous phases of oscillations in two cerebral cortical areas involved in cognitive function. We simultaneously recorded Purkinje cell (PC) single-unit spike activity in cerebellar lobulus simplex (LS) and Crus I and local field potential (LFP) activity in the medial prefrontal cortex (mPFC) and dorsal hippocampus CA1 region (dCA1). Purkinje cells in cerebellar LS and Crus I differentially represented specific phases and phase differences of mPFC and dCA1 LFP oscillations in a frequency-specific manner, suggesting a site- and frequency-specific cerebellar representation of temporal aspects of neuronal oscillations in non-motor cerebral cortical areas. These findings suggest that cerebellar interactions with cerebral cortical areas involved in cognitive functions might involve temporal coordination of neuronal oscillations. : The cerebellum has long been implicated in tasks involving precise temporal control, especially in the coordination of movements. McAfee et al. show that the cerebellar principal neurons, Purkinje cells, represent precise temporal information about the phase and phase differences of neuronal oscillations occurring in two non-motor-related cerebral cortical structures. Keywords: neuronal oscillation, cerebro-cerebellar interaction, oscillation phase, phase difference